Strategic Groups as Reference Groups: Theory, Modeling and Empirical Examination of Industry and Competitive Strategy - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 1995)
Previous studies on strategic groups have mainly focused on their static characteristics in order to test the theory of strategic groups and intraindustry performance differences (Porter, 1979; Cool and Schendel, 1988; Fiegenbaum and Thomas, 1990). In contrast, this study takes a longitudinal, dynamic perspective and describes the forces driving strategic group membership and structural evolution. It proposes that a strategic group acts as a reference point for group members in formulating competitive strategy. A partial adjustment model of strategic mobility is then developed which incorporates the idea of a strategic group as a reference group. It models strategic change in an industry both within and across strategic groups. The model is tested in the context of an in-depth industry analysis of the more significant firms in the insurance industry over the 1970-84 time period. The results suggest that strategic groups act as reference points for firm strategies and that predictions of future firm strategies and industry/group structures may also be successfully derived.